2016
DOI: 10.14405/kjvr.2016.56.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Vibrio harveyi from chub mackerel (Scomber japonicus)

Abstract: : For several days, there was a series of mortalities of chub mackerel (Scomber japonicus) that were reared for public exhibition in a private aquarium in Seoul, Korea. As part of the diagnosis of the dead fish, a bacterial isolate from the kidney was cultured, identified, and confirmed to be Vibrio (V.) harveyi using Vitek System 2 and 16S rRNA gene sequencing. Phylogenetic analysis was also performed by the neighbor-joining method. As a result, the V. harveyi isolated from chub mackerels of a private aquariu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…It was reported that the in vivo environment might affect the ability of V. harveyi to utilize sugars (Shen et al, 2017). Similar to some previous studies (Kang et al, 2014;Lee et al, 2016;Shen et al, 2017), drug sensitivity results in this study also showed that the 3 re-isolates kept the same sensitivity as 3 isolates.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported that the in vivo environment might affect the ability of V. harveyi to utilize sugars (Shen et al, 2017). Similar to some previous studies (Kang et al, 2014;Lee et al, 2016;Shen et al, 2017), drug sensitivity results in this study also showed that the 3 re-isolates kept the same sensitivity as 3 isolates.…”
Section: Discussionsupporting
confidence: 89%
“…Ampicillin, flumequine, furazolidone, oxolinic acid and sulfamethoxazole/trimethoprim were found the most effective chemicals to vibriosis treatment by Korun and Timur (2008). In another study, Lee et al (2016) determined that V. harveyi strains were resistant to fluoroquinolones. In this study, we determined that all strains were found resistant against erythromycin, kanamycin and ampicillin and the isolates were sensitive and intermediary sensitive to flumequine, oxytetracycline, florphenicol, chloromphenicol, sulfamethoxazole/ trimethoprim, ciprofloxacine, enrofloxacine, therefore they can be suggested to use in disease control.…”
Section: Resultsmentioning
confidence: 99%
“…Vibrio harveyi is a marine Gram-negative luminous organism with a requirement for sodium chloride belong the genus Vibrio (Cano-Gomez et al, 2009). Vibrio harveyi was reported in various Sparidae family members (Balebona et al, 1998, Pujalte et al, 2003, Haldar et al, 2010 as well as cultured common dentex (Dentex dentex) (Company et al, 1999, Pujalte et al, 2003, Turgay and Karataş, 2016, sole (Solea senegalensis and Dicologoglossa cuneata) (Zorilla et al, 2003, Lopez et al, 2009 and chub mackerel (Scomber japonicus) (Lee et al, 2016). It has also become recognized as a serious cause of diseases invertebrates and especially caused important economic losses of penaeid shrimp (Austin and Zhang, 2006).…”
Section: Introductionmentioning
confidence: 99%